La gestion d’un lagon en mutation : acteurs, enjeux et recherche-action en Nouvelle-Calédonie (Pacifique sud) - Marc Léopold; Jean-Michel Sourisseau; Nathaniel Cornuet; Carine David; Arnaud Bonmarchand; Pierre-Yves Le Meur; Laetitia Lasseigne; Estelle Poncet; Marie Toussaint; Guy Fontenelle; Jean-Eudes Beuret; Nicolas Guillemot (VertigO)
This paper presents some results of an interdisciplinary research programme located on the northwest coast of New Caledonia from 2008 to 2011. This area faces rapid and significant urban and economic changes induced by an on-going major mining complex that is rooted within current political issues of the New Caledonian decolonisation process. An adaptive framework was set up to improve the knowledge on the coastal social ecological system and to better manage the uses of marine resources, including small-scale fisheries. This framework combined three complementary approaches : operational research (based on three interviewing surveys of local stakeholders), interdisciplinary studies (biological, social and law sciences) and partnership between research and development agencies. Results show that the main management challenges of the coastal uses are strongly embedded to cope with environmental, social, cultural as well as economic issues. All conditions for successful participative management are not currently met at the study area scale. However our study paves the way for action to promote initiatives of shared governance over the coastal area, building on existing or emerging local initiatives, and possibly scaling them up in the future. Directions for policy making are also suggested including territory approaches to local development.